The impact of a nutritional sports program on the amount of oxygen and flexibility of the guests of the tender house for the care of the elderly (Journal of the College of Basic Education, 2022)
The conclusion reflects the importance of the program in avoiding many serious diseases, so many studies and research have urged exercise because of its positive benefits to the health of the individual. The problem with research is that many older age groups, especially those in nursing homes, do not exercise actively. In addition to the lack of adequate awareness of the importance of food and sports programs on health and the subsequent social, economic and health outcomes that benefit society in general, the study aimed at preparing a nutritional sports program, as well as identifying the impact of the program on flexibility and the amount of oxygen in the inmates of nursing homes, the researcher used the experimental approach by designing the same group with tribal and remote tests The research community was selected in the intentional manner on a group of inmates of nursing homes and the choice was made on the tender house as the research sample was formed from (12) elderly, and after conducting reconnaissance experiments and applying tribal tests and then applying exercises were conducted remote tests, and through the results the researcher reached a set of conclusions including appropriate exercises touched ...